Performance Analysis of Signalised Intersections along Jalan Sungai Abong using SIDRA Intersection 8.0 - Razulan, Farisha Ervina; Mohd Samsudin, Siti Aziah; Abdul Halim, Nur Iryna Alem; Sanik, Mohd Erwan (Multidisciplinary Applied Research and Innovation, 2023)
Traffic engineering is a part of civil engineering that implements various engineering skills in order to attain a safe and effective mobility to the road users.  The aim of this study is to analyse the performance of signalised intersections along Jalan Sungai Abong at Bandar Maharani, Muar, Johor. Therefore, the objectives that need to be fulfilled are to identify the peak hour based on commuter volume count and to analyse the level of service of three consecutive intersections along Jalan Sungai Abong.  Data were collected using manual counting for both commuter and  turning movement data. 6 to 12 enumerators were needed for that purpose depending on the number of intersection’s approaches.  Based on the analysis, peak hour and level of service for intersections were determined. A peak hour has been identified which is from 5.15 p.m. to 6.15 p.m. with a total volume of 950 vehicles. Overall, the analysis of intersections found that the level of service F (worst) were recorded as expected during peak hour. In conclusion, aim of this study was achieved. Based on the finding, Jalan Sungai Abong’s intersections require improvement, such as provision of exclusive lane for left turning as well as applying an intelligent signalised system in order to minimise the traffic congestion.